METHODS OF PURIFYING EXTRACTION PHOSPHORIC ACID (Web of Technology: Multidimensional Research Journal, 2023)
Phosphoric acid is one of the widely used reagents in the world. Its global annual production capacity is 48.5 mln. P2O5 is tons. Phosphoric acid is used in the food industry, poultry, livestock, fishery, metallurgy and several other fields, phosphoric acid is mainly used to obtain mineral fertilizers. On its basis, double superphosphate, nutrient mono- and dicalcium phosphate, mono- and diammonium phosphate, nitroammophos, etc. are produced.